Representations of People with Down Syndrome in Selected Children’s and Young Adult Literature - Tatar, Wiktoria (Representations of Disability in Cultural Spaces, 2026)
The article discusses the genetic condition known as Down syndrome. The author examines how contemporary children’s book authors portray the challenges faced by individuals with disabilities and their families. The article also addresses the concept of fairy tale therapy and the potential it holds for introducing young readers to difficult yet important topics.